2018
DOI: 10.1186/s12879-018-3443-8
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic disease research in East Africa

Abstract: BackgroundThe East African region is endemic with multiple zoonotic diseases and is one of the hotspots for emerging infectious zoonotic diseases with reported multiple outbreaks of epidemic diseases such as Ebola, Marburg and Rift Valley Fever. Here we present a systematic assessment of published research on zoonotic diseases in the region and thesis research in Kenya to understand the regional research focus and trends in publications, and estimate proportion of theses research transitioning to peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…The exact number of human deaths due to rabies in Kenya is unknown, although estimates have been made for some regions of the country and as part of the global burden of rabies estimates 1,9,10 . A recent review of research on human and animal rabies in Kenya revealed 12 published manuscripts and four theses on rabies covering mainly knowledge attitudes and practices on rabies, dog ecology and demographics and bite exposures 11 . A formal assessment of zoonotic diseases in Kenya has placed rabies among the top five priority zoonotic diseases 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The exact number of human deaths due to rabies in Kenya is unknown, although estimates have been made for some regions of the country and as part of the global burden of rabies estimates 1,9,10 . A recent review of research on human and animal rabies in Kenya revealed 12 published manuscripts and four theses on rabies covering mainly knowledge attitudes and practices on rabies, dog ecology and demographics and bite exposures 11 . A formal assessment of zoonotic diseases in Kenya has placed rabies among the top five priority zoonotic diseases 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa remains a hotspot region with a high prevalence of these zoonotic infectious diseases (Fig. 3), causing debilitating effects on people and their livestock (Kemunto et al 2018). In addition, there are non-zoonotic infectious diseases such as peste des petits ruminants (PPR), contagious caprine pleuropneumonia (CCPP) and contagious bovine pleuropneumonia (CBPP) which further exacerbate livestock problems and losses among pastoralists in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports about the emergence of infectious diseases in most of sub-Saharan Africa are linked to zoonotic infectious diseases. The frequency and trend of the emergence and re-emergence of diseases such as Ebola, Marburg, Rift Valley fever and anthrax appear to be on the rise (Kemunto et al 2018). Several risk factors catalyse the transmissibility of zoonotic infectious diseases, including livestock slaughter, handling and preparation of animal-origin food and consumption of such animal products, especially when improperly cooked or in their raw form (Mangesho et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The World Bank estimated that 6 major zoonotic disease epidemics during 1997-2009 resulted in an economic loss of more than $80 billion [1]. Controlling zoonotic disease outbreaks has become ever more important, it has been estimated that since 1940, about 40% of the emerging infectious diseases affecting humans globally, but mainly in developing countries, have originated from animals, both domestic and wild [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the interaction between wildlife, domestic animals, and humans increases the chance of zoonotic disease transmission. The sub-Saharan region was identified as one of the hotspot regions with a high prevalence of endemic zoonotic diseases and where it has a large rural population that lives in close proximity with livestock and wildlife [6,7]. In some parts of the sub-Saharan countries such as Zimbabwe, they still have problems regarding the control of zoonoses, mainly due to the lack of enough infrastructure and resources for disease surveillance [7].…”
Section: Introductionmentioning
confidence: 99%